Non-immune hydrops fetalis complicating bronchopulmonary sequestration: A case report - Jui Mandke; Vandana Bansal; Pradeep Shenoy; Haribalakrishna Balasubramanian (EL-Med-Pub, 2021)
Background: Non-immune hydrops (NIH) associated with bronchopulmonary sequestration (BPS) is quite rare with a 95% risk of intrauterine fetal death, without a fetal intervention. Case Presentation: We describe a case of an antenatally diagnosed extralobar BPS with severe NIH, who underwent fetal thoracentesis, but had worsening of NIH requiring an emergency cesarean section. Postnatally, the baby required skillful intensive care management and timely surgical management in the form of a sequestrectomy. Conclusion: We report the smallest neonate with antenatally diagnosed NIH complicating BPS treated successfully by early neonatal surgery.